2017
DOI: 10.1149/2.0011708jes
|View full text |Cite
|
Sign up to set email alerts
|

Intervalence Charge Transfer of the Nb(V)/Nb(IV) Redox Couple in Alkali Chloride Melts: Experiment and Quantum-Chemical Calculations

Abstract: The standard rate constants of charge transfer (k s ) for the Nb(V)/Nb(IV) redox couple in KCl-NbCl 5 and CsCl-NbCl 5 chloride melts have been determined. The redox process in the NaCl-KCl-NbCl 5 melt was shown being reversible; hence, the determination of k s appeared impossible. Values of k s in the KCl-NbCl 5 melt are larger than in the CsCl-NbCl 5 melt. Previously, a quantum-chemical calculations of nM + · [NbCl 6 ] model systems (M = Na, K, Cs), containing a complex anion with cations outer-sphere (OS) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…However, it seems impossible to predict the influence of the second coordination sphere on the standard rate constants of charge transfer a priori. In our previous studies for the Nb(V)/Nb(IV) redox couple 58,59 and for the Cr (III)/Cr(II) redox couple 60,61 the nonmonotonic changes of the standard rate constants were established too. Ab initio calculations performed using the quantum-chemical PC Gamess/Firefly program showed that the charge transfer activation energy can vary nonmonotonically in the Na + -K + -Cs + series in accordance with the reorganization energy ratio.…”
Section: Resultsmentioning
confidence: 99%
“…However, it seems impossible to predict the influence of the second coordination sphere on the standard rate constants of charge transfer a priori. In our previous studies for the Nb(V)/Nb(IV) redox couple 58,59 and for the Cr (III)/Cr(II) redox couple 60,61 the nonmonotonic changes of the standard rate constants were established too. Ab initio calculations performed using the quantum-chemical PC Gamess/Firefly program showed that the charge transfer activation energy can vary nonmonotonically in the Na + -K + -Cs + series in accordance with the reorganization energy ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical behavior of niobium was investigated in melts of different composition and with utilization of different working electrode. [36][37][38][39][40][41][42][43] To the best of our knowledge, the usage of working electrode made from carbopyroceram has not been previously reported. In the present study, the electrochemical behavior of niobium in chloride-fluoride melt with utilization of working electrode from carbopyroceram was investigated.…”
mentioning
confidence: 99%
“…[6][7][8] The electrochemical behavior of niobium in chloride-fluoride and fluoride melts has been the subject of numerous works. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Electrochemical studies showed that in these melts the electroreduction of Nb(V) complexes to the metal consists of two stages:…”
mentioning
confidence: 99%